2014
DOI: 10.1002/jbt.21568
|View full text |Cite
|
Sign up to set email alerts
|

Carbofuran Induced Oxidative Stress Mediated Alterations in Na+‐K+‐ATPase Activity in Rat Brain: Amelioration by Vitamin E

Abstract: Pesticides cause oxidative stress and adversely influence Na(+)-K(+)-ATPase activity in animals. Since impact of carbofuran has not been properly studied in the mammalian brain, the ability of carbofuran to induce oxidative stress and modulation in Na(+)-K(+)-ATPase activity and its amelioration by vitamin E was performed. The rats divided into six groups received two different doses of carbofuran (15% and 30% LD50) for 15 days. The results suggested that the carbofuran treatment caused a significant elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Further, H 2 O 2 molecules get converted into nontoxic water and molecular oxygen by catalase. So any alteration occurring in the activities of SOD and catalase may cause serious pathophysiological alterations in the brain [ 29 ]. The significant reduction in the activities of these enzymes at both doses of carbofuran in rat brain (present investigation) showed the failure of antioxidant defense system due to the repeated oral treatment of carbofuran for 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Further, H 2 O 2 molecules get converted into nontoxic water and molecular oxygen by catalase. So any alteration occurring in the activities of SOD and catalase may cause serious pathophysiological alterations in the brain [ 29 ]. The significant reduction in the activities of these enzymes at both doses of carbofuran in rat brain (present investigation) showed the failure of antioxidant defense system due to the repeated oral treatment of carbofuran for 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Carbofuran (C 12 H 15 NO 3 ; 2,3-dihydro-2,2-dimethyl-7-benzofuranol methylcarbamate), commonly known as furadan, is a carbamate pesticide used in farm practices to increase crop productivity. It is also used as an insecticide, nematicide and acaricide due to its short half life in the environment (Gupta, 1994, Gupta et al, 2000, Jaiswal et al, 2014). Carbofuran being a broad spectrum pesticide is ubiquitously used to protect agricultural and house hold items.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, we have reported the increased oxidative stress and its amelioration by vitamin C in the different tissues of carbofuran treated rats [11] , [12] , [13] , [14] . Vitamin E [15] and Curcumin [14] have also been reported to be potent ameliorative antioxidants against carbofuran induced toxicity.…”
Section: Introductionmentioning
confidence: 99%